2020
DOI: 10.1002/jemt.23543
|View full text |Cite
|
Sign up to set email alerts
|

Morphological assessment of glutamate zerovalent iron nanoparticles by scanning electron microscopy and its combined effect with indole acetic acid on amelioration of lead toxicity in maize (Zea mays L.)

Abstract: Food safety is a priority issue for sustainable global development that can be affected by heavy metals, contributing to morbidity and even mortality in crop growth. Heavy metals often accumulate in the soil due to the use of extensive chemical fertilizers and pesticides; therefore, the current experiment was aimed to determine the effect of glutamate zerovalent iron nanoparticles (Glu-ZVFeNPs) and indole acetic acid (IAA) on physiological mechanism of lead (Pb +2) stress tolerance at 4 and 8 ppm in Zea mays v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…The SEM showed the average particle size around 90 nm, the particle was of roughly spherical in shape which were uniformly dispersed, observation showed that the uniform distribution of particles indicating a high surface area suitable for adsorption properties. Our results are confirmed by earlier report of Saeed et al (2020).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The SEM showed the average particle size around 90 nm, the particle was of roughly spherical in shape which were uniformly dispersed, observation showed that the uniform distribution of particles indicating a high surface area suitable for adsorption properties. Our results are confirmed by earlier report of Saeed et al (2020).…”
Section: Discussionsupporting
confidence: 94%
“…The highest level of salinity resulted in the greatest reduction in maize germination percentage, germination rate, and SVI as agreed with the results obtained by Shah et al (2021). Nit‐AgNPs and IAA accumulates in plant and enables it to show resistance to salinity stress (Saeed et al, 2020). Both physiological and biochemical measures in maize showed significant changes in the current study's findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Li et al discovered that foliar application of iron-based nanoparticles, such as Fe and Fe 3 O 4 , significantly increased the chlorophyll content, net photosynthetic rate, and biomass in maize plants [65]. Saleha's study further indicated that foliar application of appropriate concentrations of glutamic acid-modified trivalent iron nanoparticles (Glu-ZVFe NPs) and indole acetic acid (IAA) enhanced root length, leaf area, and germination rate in maize, reducing the toxic effects of lead ions [66]. Some Fe 3 O 4 NPs found in chloroplast thylakoids may envelop chloroplast surfaces in the Fe 3 O 4 NP-chloroplast system, acting as both electron donors and acceptors instead of releasing iron, enhancing photosynthesis.…”
Section: Impact Of Iron-based Nanomaterials On Gramineae Plantsmentioning
confidence: 96%